A computational approach for predicting plant canopy induced wind effects on the trajectory of golf shots - Yaghoobian, N.; Mittal, R. (Sports Engineering, 2018)
Large-eddy simulation of atmospheric flow is combined with golf ball trajectory modeling that incorporates local plant canopy information to predict the trajectory of a golf shot at any hole on a golf course in a variety of wind conditions. The model is applied to examine golf shots on hole 12 of the Augusta National Golf Club, which is particularly well known for its wind-induced difficulty. The results indicate that the tree canopies around this hole play a significant role in golf ball trajectories and also induce a strong directional sensitivity on the landing spot of the ball for this hole.